Comparison the Performance of two Wireless Sensor Networks protocols (LEACH and EAMMH) - Rana Hussain; Rana Hussain (University of Thi-Qar Journal of Science, 2019)
In Spite of advantages of using wireless sensor networks in many fields , lifetime of nodes and how energyconsumption in each node it is one of the most important problems of this type of networks ,so developers of networksrelied on the use of protocols helps reduce the energy consumption of nodes in the network. Therefore aims of thisresearch is to compare the efficiency of the most popular protocols that used in wireless sensor network its (LEACH andEAMMH) has been adopted in several scenario and brief analysis of the simulation results against known metrics withenergy and network lifetime being major among them to measure the efficiency of these two protocols. In this paperwill the results and observations made from the analyses of results about these protocols are presented.